Lock and key - Dessen, Sarah (Viking, 2008)
When she is abandoned by her alcoholic mother, high school senior Ruby winds up living with Cora, the sister she has not seen for ten years, and learns about Cora's new life, what makes a family, how to allow people to help her when she needs it, and that she too has something to offer others.